Viktor E. Frankl - Gesammelte Werke: Psychotherapie, Psychiatrie und Religion Über das Grenzgebiet zwischen Seelenheilkunde und Glauben - Batthyany, Alexander (2018)
The fifth Volume of the Edition of the Collected Works of Viktor Frankls unites Frankl's writings, notes, lectures and interviews on the border area of psychology, psychiatry, and religion.